Cosmic queuing: Galaxy satellites, building blocks and the hierarchical clustering paradigm - Lagos, Claudia P. del (2009)
We study the properties of building blocks (BBs; i.e. accreted satellites) and surviving satellites of present-day galaxies using the semi-analytic model of galaxy formation SAG ('semi-analytic galaxies') in the context of a concordance Λ cold dark matter (ΛCDM) cosmology. We consider large number of dark matter (DM) halo merger trees spanning a wide range of masses (~1 × 1010-2.14 × 1015 M⊙). We find higher metallicities for BBs with respect to surviving satellites, an effect produced by the same processes behind the build up of the mass-metallicity relation. We prove that these metallicity differences arise from the higher peak height in the density fluctuation field occupied by BBs and central galaxies which have collapsed into a single object earlier than surviving satellites. BBs start to form stars earlier, during the peak 3/13/2011 ΛCDM, and build up half of their final stellar mass (measured at the moment of disruption) up to four times faster than surviving satellites. Surviving satellites keep increasing their stellar masses rather quiescently down to z ≃ 1. The difference between the metallicities of satellites, BBs and central galaxies depends on the host DM halo mass, in a way that can be used as a further test for the concordance cosmology.